Targeted degradation of MERTK and other TAM receptor paralogs by heterobifunctional targeted protein degraders - Gadiyar, Varsha; Patel, Gopi; Chen, Jesse; Vigil, Dominico; Ji, Nan; Campbell, Veronica; Sharma, Kirti; Shi, Yatao; Weiss, Matthew M.; Birge, Raymond B.; Davra, Viralkumar (Frontiers in Immunology, 2023)
TAM receptors (TYRO3, AXL, and MERTK) comprise a family of homologous receptor tyrosine kinases (RTK) that are expressed across a range of liquid and solid tumors where they contribute to both oncogenic signaling to promote tumor proliferation and survival, as well as expressed on myeloid and immune cells where they function to suppress host anti-tumor immunity. In recent years, several strategies have been employed to inhibit TAM kinases, most notably small molecule tyrosine kinase inhibitors and inhibitory neutralizing monoclonal antibodies (mAbs) that block receptor dimerization. Targeted protein degraders (TPD) use the ubiquitin proteasome pathway to redirect E3 ubiquitin ligase activity and target specific proteins for degradation. Here we employ first-in-class TPDs specific for MERTK/TAMs that consist of a cereblon E3 ligase binder linked to a tyrosine kinase inhibitor targeting MERTK and/or AXL and TYRO3. A series of MERTK TPDs were designed and investigated for their capacity to selectively degrade MERTK chimeric receptors, reduce surface expression on primary efferocytic bone marrow-derived macrophages, and impact on functional reduction in efferocytosis (clearance of apoptotic cells). We demonstrate proof-of-concept and establish that TPDs can be tailored to either selectivity degrade MERTK or concurrently degrade multiple TAMs and modulate receptor expression in vitro and in vivo. This work demonstrates the utility of proteome editing, enabled by tool degraders developed here towards dissecting the therapeutically relevant pathway biology in preclinical models, and the ability for TPDs to degrade transmembrane proteins. These data also provide proof of concept that TPDs may serve as a viable therapeutic strategy for targeting MERTK and other TAMs and that this technology could be expanded to other therapeutically relevant transmembrane proteins.